Effect of a High-intensity Interval Training method on maximum oxygen consumption in Chilean schoolchildren - Galdames-Maliqueo, Sergio; Huerta-Ojeda, Álvaro; Chirosa-Ríos, Luis; Cáceres-Serrano, Pablo; Reyes-Amigo, Tomás Rodolfo (Universidad y Salud, 2017)
Introduction: The low levels of maximum oxygen consumption (VO2max) evaluated in Chilean schoolchildren suggest the startup of trainings that improve the aerobic capacity. Objective: To analyze the effect of a High-intensity Interval Training method on maximum oxygen consumption in Chilean schoolchildren. Materials and methods: Thirty-two high school students from the eighth grade, who were divided into two groups, were part of the study (experimental group = 16 students and control group = 16 students). The main analyzed variable was the maximum oxygen consumption through the Course Navette Test. A High-intensity Interval training method was applied based on the maximum aerobic speed obtained through the Test. A mixed ANOVA was used for statistical analysis. Results: The experimental group showed a significant increase in the Maximum Oxygen Consumption between the pretest and posttest when compared with the control group (p < 0.0001). Conclusion: The results of the study showed a positive effect of the High-intensity Interval Training on the maximum consumption of oxygen. At the end of the study, it is concluded that High-intensity Interval Training is a good stimulation methodology for Chilean schoolchildren.